No-waiting dentine self-etch concept—Merit or hype - Huang, Xue-qing; Pucci, César R. [UNESP]; Luo, Tao; Breschi, Lorenzo; Pashley, David H.; Niu, Li-na; Tay, Franklin R. (Elsevier, 2017)
Objective A recently-launched universal adhesive, G-Premio Bond, provides clinicians with the alternative to use the self-etch technique for bonding to dentine without waiting for the adhesive to interact with the bonding substrate (no-waiting self-etch; Japanese brochure), or after leaving the adhesive undisturbed for 10 s (10-s self-etch; international brochure). The present study was performed to examine in vitro performance of this new universal adhesive bonded to human coronal dentine using the two alternative self-etch modes. Methods One hundred and ten specimens were bonded using two self-etch application modes and examined with or without thermomechanical cycling (10,000 thermal cycles and 240,000 mechanical cycles) to simulate one year of intraoral functioning. The bonded specimens were sectioned for microtensile bond testing, ultrastructural and nanoleakage examination using transmission electron microscopy. Changes in the composition of mineralised dentine after adhesive application were examined using Fourier transform infrared spectroscopy. Results Both reduced application time and thermomechanical cycling resulted in significantly lower bond strengths, thinner hybrid layers, and significantly more extensive nanoleakage after thermomechanical cycling. Using the conventional 10-s application time improved bonding performance when compared with the no-waiting self-etch technique. Nevertheless, nanoleakage was generally extensive under all testing parameters employed for examining the adhesive. Conclusion Although sufficient bond strength to dentine may be achieved using the present universal adhesive in the no-waiting self-etch mode that does not require clinicians to wait prior to polymerisation of the adhesive, this self-etch concept requires further technological refinement before it can be recommended as a clinical technique. Clinical significance Although the surge for cutting application time to increase user friendliness remains the most frequently sought conduit for advancement of dentine bonding technology, the use of the present universal adhesive in the no-waiting self-etch mode may not represent the best use of the adhesive.
Keywords: Dentine; Self-etch; Time factors; Universal adhesives